Two-way signalling through the LFA-1 lymphocyte adhesion receptor. - Dustin, M (1990)
T lymphocyte recognition of foreign antigens and migration throughout the body require the regulated adhesion of lymphocytes to diverse types of cells and to the extracellular matrix. The lymphocyte adhesion 'receptor' LFA-1, a member of the integrin family, interacts with ICAM-1 and other counter-receptors to mediate adhesion. The LFA-1/ICAM-1 interaction is regulated by signals transmitted from the cytoplasm to the extracellular space. Conversely, LFA-1 transmits signals from the extracellular space to the cytoplasm to regulate T lymphocyte activation. The observed properties of LFA-1 and related adhesion 'receptors' are incorporated into a general model for adhesion during immune surveillance and recognition of foreign antigens.